2018
DOI: 10.2337/dc17-2530
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cardiovascular Disease and Death in Individuals With Prediabetes Defined by Different Criteria: The Whitehall II Study

Abstract: Prediabetes defined by HbA was associated with a worse prognosis than prediabetes defined by FPG or 2hPG. However, the excess risk among individuals with prediabetes is mainly explained by the clustering of other cardiometabolic risk factors associated with hyperglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 35 publications
(35 reference statements)
5
86
0
9
Order By: Relevance
“…Patients with CAD but without apparent glucose abnormalities were recommended to evaluate their glycemic state [36]. Prediabetes was associated with a worse prognosis in individuals with stable CAD only when combined with other cardiometabolic disorders [37][38][39]. Several previous studies demonstrated that the measurement of Fib provided incremental value to risk assessment in CAD patients with DM.…”
Section: Fib and Cardiovascular Outcomes In Patients With Coronary Armentioning
confidence: 99%
“…Patients with CAD but without apparent glucose abnormalities were recommended to evaluate their glycemic state [36]. Prediabetes was associated with a worse prognosis in individuals with stable CAD only when combined with other cardiometabolic disorders [37][38][39]. Several previous studies demonstrated that the measurement of Fib provided incremental value to risk assessment in CAD patients with DM.…”
Section: Fib and Cardiovascular Outcomes In Patients With Coronary Armentioning
confidence: 99%
“…Specifically, in a meta-analysis of prospective cohort studies, Huang et al (43) found that for those patients with prediabetes (defined by various impaired fasting glucose and impaired glucose tolerance criteria), the range of relative risks for composite CVD was 1.13 to 1.30, coronary heart disease 1.10 to 1.20, stroke 1.06 to 1.20, and all-cause mortality 1.13 to 1.32. Interestingly, in the Whitehall II Study, the incidence rate for major CVD events was greater for those patients with prediabetes diagnosed by A1C compared with either FPG or 2-hour postchallenge glucose (81).…”
Section: The Specific Context Of Dbcd As the Insulin Resistance-predimentioning
confidence: 97%
“…Az általánosan használt, a hivatalos WHOdefinícióban azonban előbb a "köztes hyperglykaemia", 5 majd a "diabetes fokozott kockázatával járó állapotok" 6 nevet viselő meghatározás a szénhidrátanyagcsere-zavarok azon formáit jelöli, amelyekben az éhomi és/vagy a glukózterhelést követően mért vércukorszint magasabb a még normálisnak tekintettnél, de nem éri el a diabetest kórjelző mértéket. 2,4,5,6 Míg a meghatározásban egységes, formái és az egyes formák definiálása tekintetében eltér az európai (WHO/IDF) és az amerikai (ADA) álláspont.…”
Section: A Prediabetes Fogalma Formáiunclassified
“…Az amerikai irányelvek szerint a még normális éhomi vércukorszint felső határa alacsonyabb a WHO állásfoglalásában szereplőnél (≤5,5 vs. ≤6,0 mmol/l), ennek megfelelően az IFG éhomi vércukortartománya is különbözik (5,6-6,9 vs. 6,1-6,9 mmol/l). 4 Ennek oka az amerikai felnőtt lakosság körében észlelt túlsúly/elhízás és a következményes szénhidrátanyagcsere-zavar, valamint az ennek révén fokozott keringési kockázattal rendelkezők kiugróan magas aránya. Az IFG és az iIGT patogenezise eltérő.…”
Section: A Prediabetes Fogalma Formáiunclassified
See 1 more Smart Citation